EU MEMBERSHIP IN INTERNATIONAL ORGANIZATIONS IN THE CONTEXT OF ITS PERSONALITY - I. M. Lifshits (Московский журнал международного права)
Introduction. Personality of the EU as well as of the any international organization is based on the provisions of its founding treaties. Wide range of internal powers transferred by Member States to the EU predefined its activities in the international plane including signing of international agreements and membership in international organizations. Legal infrastructure of such membership is the result of peculiarities of the EU as the union of the states, powers of the EU institutions, and phenomenon of the simultaneous membership in the IOs of the EU and Member States, as well as of legal specificity of certain IO. All these matters have become a subject of the research.Materials and methods. Author researched case law of the Court of Justice of the European Union including last jurisprudence as well as international agreements and works of the Russian and foreign scholars. The methodological basis of the research contains general scientific and special methods.Research results. EU competence has been largely interpreted by the CJEU which has established a concept of parallel powers. This concept was based on the doctrine of implied powers. It means that execution of the internal powers in certain sphere assumes the external powers including signing of international agreements and IO membership in the same sphere. Lisbon Treaty absorbed provisions of the CJEU case-law relating to EU external competence, and the last Court’s jurisprudence reflects the further development of the implied powers doctrine.Discussion and conclusions. EU institutions, first of all the CJEU and the Commission, tend to consolidate the international voice of the Member States, to limit the external capacity of the Member States, and this activity results in so called ‘‘europesation’’ of the international legal order. When the evident legal base for transfer of Member State external powers to the EU institutions is lacking, the CJEU utilizes the principle of sincere cooperation stipulated in Art. 4 of the TEU. The CJEU jealously safeguards it monopoly in the EU legal order and does not permit (save to the certain exceptions) to conclude international agreements which provide for jurisdiction of other tribunals. Basing on the EU constitutional order and its autonomy rhetoric the CJEU established a general principle that all the relations between the EU Member States should stand exclusively on the EU Law.